THE IMPLICATION OF ADDITIONAL PRACTICE FOR EFL LEARNERS IN WRITING SKILL ASSESSMENT - Harnani - Harnani (English Journal Literacy Utama, 2020)
Additional material or practice is highly needed in language learning and teaching in order to progress as expected. However, its usage and delivery frequency may differ and to a certain extent may affect the language assessment for EFL students. This study outlines the effect of providing various and frequent additional writing practice to language assessment. The aim of the study is twofold, firstly, it is to identify the implication of adding more practice, aside from theprovided materials, to writing skill assessment, and secondly, to examine whether uniformity exists among the teachers in choosing the added practice and the frequency in providing it and how this uniformity influences the expected assessment. This study applied a qualitative method and used questionnaire, interview and lesson observation as the instruments. The result of the analyzed data showed that the various additional writing practice could well be one of contributing factors to the inconsistency in writing skill assessment for intermediate level EFL students. The data also showed that there was no uniformity among the teachers in choosing the additional writing practice and the frequency in providing it, which may also have resulted an implication in writing assessment.Agreement among teachers in creating and selecting a number of identical practice and sustaining the frequency in delivering it may propose a consistency in writing skill assessment.